Asuhan Kebidanan Continuity of Care Nn. N Umur 17 Tahun di BPM Wijayanti dengan Anemia Ringan - Wijayanti; Vistra Veftisia (Universitas Ngudi Waluyo, 2024)
Continuity of care is the provision of obstetric care starting from pregnancy, childbirth, postpartum, neonate to deciding to use family planning. This aims to help, monitor, and detect the possibility of complications that accompany the mother and baby from pregnancy to the use of birth control. The midwifery care method at PMB Wijayanti is through home visits by providing counseling according to the needs of the mother. Midwifery care given to Mrs.